Chemical Rescue of α3-Galactosyltransferase. Implications in the Mechanism of Retaining Glycosyltransferases - Monegal, Ana; Planas, Antoni (Journal of the American Chemical Society, 2006)
The mechanism of retaining glycosyltransferases is still poorly understood and the subject of current debate. Both double displacement and front side single displacement (SNi) mechanisms have been proposed. A “chemical rescue methodology” is here applied to a retaining α3-galactosyltransferase. Azide as exogenous nucleophile rescues the activity of the inactive E317A mutant to give β-d-galactosylazide. This result fits best with a double displacement mechanism in which Glu317 is the enzyme nucleophile involved in the formation of a glycosyl-enzyme intermediate.